A discrete dislocation dynamics framework for polycrystalline materials - Chooi, Zheng Hoe (2015)
Polycrystalline materials with mean grain size smaller than 10nm will soften if its mean grain size is further reduced, deviating from Hall-Petch relation which states that yield strength is inversely proportional to square root of mean grain size. Besides, polycrystalline materials with identical mean grain size but different grain size distribution also shown to have different strength. These phenomena suggested that average grain size is not the only factor that determines the strength of polycrystals. This project aims to expand the current discrete dislocation dynamics (DDD) model to investigate the causes of the deviation in Hall-Petch relation. First, the DDD model was modified to allow simulations on arbitrary grain shapes. Simulation results showed that Johnson-Mehl microstructure (wider grain size distribution) is weaker than site-saturation microstructure (narrower grain size distribution), despite both having identical average grain size. This showed that grain size distribution does affect the strength of polycrystals. The presence of relatively larger grains in Johnson-Mehl microstructure allowed more dislocation pile up, resulting in higher plastic strain. Next, the DDD model was further expanded to incorporate grain boundary deformations. Using this model and removing influences of lattice dislocation, preliminary results obtained from regular hexagonal microstructure with grain size of 10nm was shown to be weaker than that of 20nm and 40nm. In this case, reducing grain size increased grain boundary density, consequently allowed more grain boundary deformation, weakening the material. Results obtained from the modified DDD framework are in line with experimental findings.